Molecular biology : genes to proteins - Tropp, Burton E (Jones and Bartlett Learning, 2012)
Newly revised and updated, the Fourth Edition is a comprehensive guide through the basic molecular processes and genetic phenomena of both prokaryotic and eukaryotic cells. Written for the undergraduate and first year graduate students within molecular biology or molecular genetics, the text has been updated with the latest data in the field. It incorporates a biochemical approach as well as a discovery approach that provides historical and experimental information within the context of the narrative.